Splice variants of mitofusin 2 shape the endoplasmic reticulum and tether it to mitochondria - Naón, Déborah; Hernández-Alvarez, María Isabel; Shinjo, Satoko; Wieczor, Milosz; Ivanova, Saska; Martins de Brito, Olga; Quintana, Albert; Hidalgo, Juan; Palacín, Manuel; Aparicio, Pilar; Castellanos, Juan; Lores, Luis; et al. (Science (American Association for the Advancement of Science), 2023)
In eukaryotic cells, different organelles interact at membrane contact sites stabilized by tethers. Mitochondrial mitofusin 2 (MFN2) acts as a membrane tether that interacts with an unknown partner on the endoplasmic reticulum (ER). In this work, we identified the splice variant ERMIT2 as the ER tethering partner of MFN2. Splicing of produced ERMIT2 and ERMIN2, two ER-specific variants. ERMIN2 regulated ER morphology, whereas ERMIT2 localized at the ER-mitochondria interface and interacted with mitochondrial mitofusins to tether ER and mitochondria. This tethering allowed efficient mitochondrial calcium ion uptake and phospholipid transfer. Expression of ERMIT2 ameliorated the ER stress, inflammation, and fibrosis typical of liver-specific knockout mice. Thus, ER-specific variants display entirely extramitochondrial MFN2 functions involved in interorganellar tethering and liver metabolic activities.